Arabic Language Learning Problem in Class VIII Students of MTsN 3 Ponorogo - Ajizah, Ratna Utami Nur; Putra, Khalis Zamrani; Miftahudin (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2021)
Arabic learning conducted at MTsN 3 Ponorogo has several obstacles including writing and sound grammar, so learning Arabic is considered a difficult and boring subject. The problem of sound and writing is a problem that usually arises in learning Arabic for non-Arabs, as well as experienced by class VIII students at MTsN 3 Ponorogo. This research is a qualitative descriptive study that describes Arabic learning activities with the research subjects namely teachers, students and the object of this research is Arabic subjects. The problems of learning Arabic include educator factors, student factors, method factors, media factors and learning evaluation factors. Efforts must be made to include educational training, provide understanding and motivation to students and choose appropriate teaching methods.